The book of cold cases - St. James, Simone (New York : Berkley, 2022)
When Shea Collins, who runs a true crime website, the Book of Cold Cases, gets a chance to interview Beth Greer, an infamous woman acquitted of two cold case slayings, she senses something isn$1 (Bt right and wonders if she is in the presence of a manipulative murderer.s
Keywords: Cold cases (Criminal investigation) -- Fiction; Bloggers -- Fiction; Serial murders -- Fiction; Trials (Murder) -- Fiction; Acquittals -- Fiction; Truthfulness and falsehood -- Fiction; Oregon -- Fiction; Detective and mystery fiction; Psychological fiction; Thrillers (Fiction)